2020
DOI: 10.1002/agj2.20039
|View full text |Cite
|
Sign up to set email alerts
|

Film mulching optimizes the early root and shoot development of rain‐fed spring maize

Abstract: Full ridge‐furrow plastic film‐mulching (FM) is a key agriculture drought mitigation technique in the semiarid Loess Plateau of China. The establishment of high‐yield maize (Zea mays L.) population under FM is built on robust plant development and indispensable soil support that generally started from the seedling stage. However, there is still a lack of information on the root‐shoot development of maize seedling under FM. A 2‐yr field experiment was performed in rainfed plots of Loess Plateau experimental sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 89 publications
(144 reference statements)
0
2
0
Order By: Relevance
“…As one layer of physical barrier, PM can influence soil surface temperature in the following ways: (1) PM can hinder heat exchange near the soil surface and inhibit latent heat loss caused by evaporation; (2) the long-wave solar radiation during daytime cannot pass through the mulching film and may be reflected into the air near the ground, which is converted into heat energy and raises the air temperature near the soil surface; (3) shortwave radiation can penetrate through the cover film layer to the ground, by which some is converted into heat energy, resulting in temperature increases; and (4) PM at night can inhibit long-wave radiation from the ground, reducing soil heat loss, and partially promote heat transfer to the deep soil via heat conduction [47][48][49][50]. The above cumulative effects increase the net radiant heat income and effectively increase the soil temperature.…”
Section: Mechanism Of the Warming Effect Under Pmmentioning
confidence: 99%
“…As one layer of physical barrier, PM can influence soil surface temperature in the following ways: (1) PM can hinder heat exchange near the soil surface and inhibit latent heat loss caused by evaporation; (2) the long-wave solar radiation during daytime cannot pass through the mulching film and may be reflected into the air near the ground, which is converted into heat energy and raises the air temperature near the soil surface; (3) shortwave radiation can penetrate through the cover film layer to the ground, by which some is converted into heat energy, resulting in temperature increases; and (4) PM at night can inhibit long-wave radiation from the ground, reducing soil heat loss, and partially promote heat transfer to the deep soil via heat conduction [47][48][49][50]. The above cumulative effects increase the net radiant heat income and effectively increase the soil temperature.…”
Section: Mechanism Of the Warming Effect Under Pmmentioning
confidence: 99%
“…e most significant root concentration is located at the soil surface where the soil is loose, and water, oxygen, and nutrients are most easily accessible [62]. idar et al [63] and Yao et al [54] observed that most vertically found roots were in organic and plastic mulching treatments at the top 0-30 cm soil depth and horizontally 0-15 cm distance from the plant foundation. Also, Schenk and Jackson [52] reported annual succulents had very shallow rooting depths.…”
Section: Root Developmentmentioning
confidence: 99%